The Impact of Digital Accounting Technologies on Financial Reporting Accuracy in Capital Shoppers Limited and Other Small and Medium Enterprices (SMEs) - Marc Paul Wamono (Uganda Christian University, 2024)
This study investigates the impact of digital accounting technology on financial reporting accuracy among SMEs in Uganda with a specific focus on Capital Shoppers Limited. The adoption of digital accounting technologies has become increasingly critical for improving financial accuracy and transparency within the organization. The objectives of this research are to; Establish the level of adoption of digital accounting technologies by SMEs, the accuracy level of financial reporting accuracy among SMEs, Explore the relationship between the adoption of digital accounting technologies and the accuracy of Financial reporting within SMEs. A descriptive research design was adopted, focusing on a sample size of 20 respondents from capital shoppers limited Uganda. Both quantitative and qualitative data collection methods where utilized involving surveys, interviews to gather comprehensive insight from financial managers, accountants and other relevant personnel. The study revealed a moderate level of adoption of digital accounting technologies among SMEs with a corresponding improvement in Financial reporting accuracy. However there were challenges including limited access to advanced technology and inadequate training. The research recommends that SMEs invest in modern digital accounting technologies, provide adequate training for their Staff, and develop policies that support effective use of these technologies to enhance Financial reporting. The abstract provides a concise overview of the study, highlighting the critical aspects of the research and the recommendations made to improve accounting practices within SMEs.